Effect of henna (lawsonia inermis) and juglans regia bark extract on some pathogenic microorganisms - Ali Jabbar Rashak AL-Sa'ady; Lamees Mohammed Riuadh Abbas (College of Pharmacy / Mustansiriyah University, 2018)
Six types of extracts were prepared for henna leaves (Lawsonia inermis) and Juglans Regia bark, by using distilled water, 1 M phosphate buffer (pH 7.0), 1 M sodium acetate buffer (pH 6.0), 1 M Tris-HCl buffer (pH 8.0), ethanol and methanol alcohol. The antibacterial activities of the henna and J. regia extracts were determined using the agar disc diffusion on nutrient agar for each one of Staphylococcus aureus, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli and Candida albicans. The results of the phytochemical screening of henna extract revealed the presence of alkaloids, glycosides, terpens, anthraquinones, tannins and phenols, whilst flavonoids, saponins, steroids, resins and coumarines gave negative test, on the other hand, result indicate the presence of alkaloids, glycosides, flavonoids, tannins, saponins, phenols, steroids and anthraquinones, whereas the terpens, resins, and coumarines gave negative test in J. Regia bark extract. The highest antimicrobial activity was observed upon using 10 gm % (w:v) of henna extracted by 1M phosphate buffer (pH 7.0), and 10 gm % (w:v) of J. regia bark extracted with 1M sodium acetate buffer (pH 6.0), after mixing for 4 hours. The best concentration of henna and J. regia bark extract on discs that gave the high antimicrobial activity against the tested microorganisms was 10 mg/ml.